Implementation Of The STAD Model And Asmaul Husna Card Media To Improve PAI Learning Outcomes In Class VI, Jombor Temanggung Elementary School - Hasanatun Latifah; Luluk Ifadah; Yenny Aulia Rahman; Suwandi, Mohamad Ardin (Yayasan Azhar Amanaa Yogyakarta, 2023)
Learning is dominated by lectures so that the teacher's explanation is boring. Teachers do not motivate students through learning experiences. The teacher explains the material without using media. So that causes low student learning outcomes on Asmaul Husna material. The purpose of this study was to determine the implementation of the STAD model with the Asmaul Husna card as media and to determine the increase in learning outcomes of PAI Asmaul Husna class VI semester 1 SD Negeri Jombor. This research uses a descriptive quantitative PTK type. Quantitative and qualitative data analysis techniques. Observation and test data collection techniques. This research was conducted on class VI students in semester 1 of SD Negeri Jombor Jumo Temanggung in the 2022/2023 academic year. Improvements to the learning carried out by the teacher in the classroom are using the STAD model and Asmaul Husna card media for two cycles. The difference between cycles 1 and 2 lies in the number of students in the group. In cycle 1 each group consisted of 9 students, whereas in cycle 2 each group only contained 3 students. The results showed that there was an increase in student learning outcomes in each cycle. The pre-cycle class average value was only 65.93. The improvement in cycle I increased to 75.18 and the improvement in cycle II increased to 88.33. Increasing learning outcomes for each cycle of answering the formulation of learning problems using the STAD model and Asmaul Husna card media can improve PAI learning outcomes for Asmaul Husna class VI semester 1 SD Negeri Jombor Jumo Temanggung for the 2022/2023 academic year.